Efek Pemberian Berbagai Dosis Pupuk Nitrogen terhadap Hasil dan Kualitas Umbi Kentang (Solanum tuberosum L.) - muchammad aufa achbaro; Anis Rosyidah; Sunawan Sunawan (AGRONISMA, 2021)
Nitrogen nutrients serve as chlorophyll-forming which plays an important role in the process of photosynthesis. If photosynthesis goes well then vegetative plants that form are increasing to be translocated to the tubers of plants. Nitrogen fertilization research that has been widely carried out so far only for vegetable potatoes (granola varieties) with doses depending on the location, while fertilization recommendations for processed potatoes are not yet available and will differ due to differences in desired properties. Deficiency and excess nitrogen fertilizer result in low yield and quality of tubers produced. The purpose of this study is to obtain the results and quality of potato tubers due to the administration of various doses of nitrogen fertilizers and to get optimum doses of nitrogen fertilization that can improve the yield and quality of tubers. Field experiments were conducted in Sumberejo village â€“ Batu at an altitude of 690 meters above sea level. Â Randomized Group design is applied with four treatments, namely: fertilizing nitrogen at doses of 40, 80, 120, 160 N kg ha-1 and repeated six times. The source of nitrogen fertilizer comes from ZA which is applied 2 times, at the same time of planting and 35 days after planting. The results showed that in general, the administration of nitrogen fertilizers that are getting larger to a dose of 120 kg ha-1 is able to increase chlorophyll, tan-1 tuber yield, ha-1 tuber yield, dry weight of tubers, water content, starch levels, type weight and total dissolved solids. The administration of nitrogen fertilizer doses of 119.85 kg ha-1 and 118.95 N kg ha-1 is the optimal dose to produce the results of tubers ha-1 and maximum tuber starch levels. The result of tuber ha-1 obtained by 42.16 tons ha-1 and starch content of 16.75 %.